Representation of Religiousness of Grade IX Students of MTs Al-Hidayah Guppi in Writing Short Stories and Its Utilization as an Instrument for Digital-Based Learning Assessment - Rahayu, Sri; Indrya Mulyaningsih; Tati Sri Uswati (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The study aims to improve students' ability to analyze religious values ​​and intrinsic elements in a collection of short stories written by grade IX students, using the theory of religious values ​​according to Rodney Stark and Charles Y. Glock, and to downstream the results of the analysis into an assessment instrument in the form of Quizizz. Religiosity or religious attitudes in literary works can appear in every element of the literary work. In prose literary works, religiosity can be seen from the depiction of the setting (time, place, objects), plot, story theme, and of course characterization. The research method used is descriptive qualitative. Data in the form of narrative quotes, dialogues and religious values ​​contained in the collection of short stories written by grade IX students. Based on the theory of Rodney Stark and Charles Y. Glock, five types of religious values ​​were found in the collection of short stories written by students. The results of this study indicate that the collection of short story writing of grade IX students found religious belief (belief) with a total of 5 data, religious practice (carrying out obligations) with a total of 25 data, religious feeling (appreciation) with a total of 8 data, religious knowledge (knowledge) with a total of 9 data, and religious effect (behavior) with a total of 10 data. This quiz is expected to improve students' understanding of the contents of short stories that include religious values ​​and students' understanding of intrinsic elements in short stories.